2016
DOI: 10.1021/acs.langmuir.6b01766
|View full text |Cite
|
Sign up to set email alerts
|

Hidden Nanobubbles in Undersaturated Liquids

Abstract: Here, we propose theoretically the existence of a new type of nanobubble in undersaturated liquids. These nanobubbles have a concave vapor-liquid interface featured with a negative curvature rather than a positive curvature for nanobubbles in supersaturated liquids, so that they often hide inside of the substrate textures and it might not be easy to characterize them through atomic force microscopy (AFM) measurements. However, these hidden nanobubbles are still stabilized by the contact line pinning effect and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 61 publications
2
5
0
Order By: Relevance
“…178 Literature often suggests that they can only occur in supersaturated gas solutions 187 and that their cavitation is only related to pressure gradients and variations, contrary to temperature change, 192 yet this is opposed by experimental and theoretical reports. 189,193,194 While most research on this topic is performed with water, nanobubbles have also been reported for aqueous ethanol solutions 195 and protic nonaqueous solvents. 196 Bulk phase nanobubbles can be as small as 10 nm in diameter, 179 but typical sizes range between 100 and 300 nm.…”
Section: Bubble Mechanism: the Existential Crisis Of Nanobubblesmentioning
confidence: 99%
“…178 Literature often suggests that they can only occur in supersaturated gas solutions 187 and that their cavitation is only related to pressure gradients and variations, contrary to temperature change, 192 yet this is opposed by experimental and theoretical reports. 189,193,194 While most research on this topic is performed with water, nanobubbles have also been reported for aqueous ethanol solutions 195 and protic nonaqueous solvents. 196 Bulk phase nanobubbles can be as small as 10 nm in diameter, 179 but typical sizes range between 100 and 300 nm.…”
Section: Bubble Mechanism: the Existential Crisis Of Nanobubblesmentioning
confidence: 99%
“…Tuziuti et al had also suggested, in the conclusion of their paper, that stable nanobubbles may exist in liquids undersaturated in gas. This hypothesis had previously been put forward by Guo et al [19] .…”
Section: Accepted Manuscriptmentioning
confidence: 80%
“…Nanobubble nucleation at surfaces has been shown to be possible even at low levels of overgassing (100-120%) with a temperature change of a few degrees around room temperature inhibiting or promoting nanobubble formation [75]. The presence of nanopits or crevices has been found to increase nanobubble stability [76,77], large holes in supported 2D membranes would play this role in the nanopore system. The mechanism of nanobubble nucleation and stability on 2D materials is something which would require further study, especially the role of surface contaminants.…”
Section: Bubbles With 2d Materialsmentioning
confidence: 99%